1994
DOI: 10.1007/bf01091224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of purslane (Portulaca oleracea)

Abstract: Purslane (Portulaca oleracea), grown under greenhouse conditions, was harvested at three growth stages and analyzed for total solids, total protein, ash, soluble carbohydrate, and fructose/fructane in whole plants, leaves, stems, and roots. Significant increases were observed in total solids and protein during plant maturation. Leaves had the highest amount of protein in the third growth stage (44.25 g/100 g dry matter). Roots showed a decline in protein level as the plant aged. Soluble carbohydrate was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 8 publications
3
60
0
2
Order By: Relevance
“…This plant also contains vitamins (mainly vitamins A, C and some vitamin B) [2,3] . The plant also contains organic acids such as citric, maleic, cyanuric, caffeic acid as well as flavonoids, coumarins, and glycosides [4] .…”
Section: Hashemzehi Et Al: Effect Of Portulaca Oleracea On Musacrinmentioning
confidence: 99%
See 1 more Smart Citation
“…This plant also contains vitamins (mainly vitamins A, C and some vitamin B) [2,3] . The plant also contains organic acids such as citric, maleic, cyanuric, caffeic acid as well as flavonoids, coumarins, and glycosides [4] .…”
Section: Hashemzehi Et Al: Effect Of Portulaca Oleracea On Musacrinmentioning
confidence: 99%
“…This plant also contains vitamins (mainly vitamins A, C and some vitamin B) [2,3] . The plant also contains organic acids such as citric, maleic, cyanuric, caffeic acid as well as flavonoids, coumarins, and glycosides [4] .P. oleracea has several therapeutic effects including diuretic, antiascorbic, antipyretic, antiinflammatory [5][6][7] .…”
mentioning
confidence: 99%
“…The purslane tea made by roasting process showed about 7% moisture, 3.47% crude lipids, 20.82% crude protein and 54.78% crude fiber (28). Also, because the purslane shows differences for the nutrient components depending on its maturity, it is known that the intake of sprouts is effective in terms of minerals and the ω-3 fatty acids (29).…”
Section: Nutritional Components Of Purslanementioning
confidence: 99%
“…Bangash et al (2011), Hussain et al (2011, Mohamed and Hussein (1994) also reported their findings about the highest amount of Potassium (P) but got different results regarding other minerals.…”
Section: Discussionmentioning
confidence: 98%